Pembinaan Ibadah Melalui Kegiatan PKL: Studi Kegiatan Membaca Al-Qur’an dan Sholat Berjamaah di Masjid Sibau Hulu, Kecamatan Putussibau Utara, Kabupaten Kapuas Hulu - Hardimansyah Hardimansyah; Ria Suryati; Anggun Dwi Zdulhana; Lisa Misfuwati; M. Faisal Chandra; Rahmad Maulana; Muhammad Marwan; Alif Faqih Hidayatulloh Setiyoko (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to describe the implementation of worship training through fieldwork practice (PKL) activities carried out at the Sibau Hulu Mosque. The focus of the activities includes reading the Qur'an and performing congregational prayers as an effort to strengthen religious values ​​and foster spiritual discipline within the community. The method used in this study is a descriptive qualitative approach with observation, participation, and documentation techniques during the Qur'an reading and congregational prayers activities, which provide a positive contribution in increasing worship awareness, forming better worship habits, and strengthening social interactions among mosque congregations. In addition, this activity also encourages active participation, cooperation, and internalization of Islamic values ​​in daily life. Thus, religious-based PKL activities have an important role in supporting worship training and spiritual character formation within the Sibau Hulu Mosque community, which in turn can strengthen Islamic brotherhood at the local level. This activity is also expected to serve as a model for other mosques in improving worship development and spiritual character of the congregation.